Mystical Dimensions of Morality in the Selected Short Stories of Jalāl al-Dīn Rūmī - Homam, Dr; Muhammad Naqib bin Othman (IIUM Journal of Religion and Civilisational Studies, 2022)
Jalāl al-Dīn Rūmī’s works are famous for educating readers regarding morality. They have been read and quoted by various people from different backgrounds. However, it is easy to misinterpret the messages in his works, especially his short stories, as they appeal to a wider audience. This study examines the mystical dimension of morality in Rūmī’s short stories. The study was conducted using a critical moral approach, which analyses the moral messages that are present in five selected short stories found in Rūmī’s Mathnawi. The moral messages in the selected short stories are analysed based on several examples of moral characteristics that are defined by al-Qushayrī, using textual analysis. The analysis shows that Rūmī’s moral messages in his short stories are related to the journey of a Sufi on the path. The moral messages can be connected to the characteristics of a good Sufi that are described by al-Qushayrī. Additionally, this study found that the characteristics of Sufi morality described by Rūmī show its superiority against other moral theories.